Corporate Image and Customer Loyalty of Nigeria Ports Authority in Rivers State - OLUMATI, I. F.; OZURU, H. N. (International Journal on Economics, Finance and Sustainable Development, 2022)
This study examined the relationship between Corporate Image and Customer Loyalty of Nigeria Ports Authority in Rivers State. Nowadays, building corporate image has become a priority for organization to grow their business competitively. With increasing competition between ports, attracting new customers can no longer guarantee profits and success, but retaining existing customers is of more importance. In fact, a competitive environment provides customers with more alternatives to choose from. The study aimed at investigating the influence of Corporate Image on Customer Loyalty of Nigeria Ports Authority in Rivers State. The study adopted the survey research design. The study population comprised of 200 customers of Nigerian Ports Authority which were conveniently sampled. After data cleaning, 174 copies of questionnaire were completed and returned. Spearman’s Rank Order Correlation Coefficient via SPSS 21.0 version was used to test the seven hypotheses. Findings revealed that there was a positive relationship between service quality and customer loyalty; physical evidence and customer loyalty. In conclusion, we stated that loyal customers are more likely to repurchase the same service or brand, provide positive word-of-mouth and be willing to pay a premium price.